Optimization of Saccharomyces boulardii production in solid-state fermentation with response surface methodology - Hu, Yuanliang; Qin, Huanhuan; Zhan, Zhichun; Dun, Yaohao; Zhou, Ying; Peng, Nan; Ling, Huayun; Liang, Yunxiang; Zhao, Shumiao (Biotechnology, biotechnological equipment, 2016)
Saccharomyces boulardii preparations are promising probiotics and clinical agents for animals and humans. This work focused on optimizing the nutritional conditions for the production of S. boulardii in solid-state fermentation by using classical and statistical methods. In single-factor experiments, the S. boulardii production was significantly increased by the addition of glucoamylase and the optimal carbon and nitrogen sources were found to be soluble starch and NH 4 Cl, respectively. The effects of the glucoamylase, soluble starch and NH 4 Cl on S. boulardii production were evaluated by a three-level three-factor Box-Behnken design and response surface methodology (RSM). The maximal yeast count (4.50 ×10 9 CFU/g) was obtained under the optimized conditions (198 U/g glucoamylase, 2.37% soluble starch and 0.9% NH 4 Cl), which was in a good agreement with the predicted value of the model. This study has provided useful information on how to improve the accumulation of yeast cells by RSM.